The Learning Curve Does Not Affect Positive Surgical Margin Status in Robot-Assisted Laparoscopic Prostatectomy - Islamoglu, Ekrem; Karamik, Kaan; Ozsoy, Cagatay; Tokgoz, Husnu; Ates, Mutlu; Savas, Murat (Urology Journal, 2018)
Purpose: To assess the oncologic results of our robot-assisted laparoscopic prostatectomy (RALP) cases and investigate whether the learning curve (LC) affects the oncological outcomes. Materials and Methods: Between March 2015 and September 2017, 111 patients underwent RALP by a single surgeon in our clinic. The learning curve was analyzed using the moving average method. We compared the rate of positive surgical margins(PSM) and oncological outcomes, operation times, hematocrit changes and duration of hospitalization among the patients during and after the LC. Complications were also noted according to Clavien system. Results: LC analysis using the moving average method showed that the LC stabilized between cases 51–60. So, patients were classified into two groups; 1-50 cases (Group 1) and 51-111 cases (Group 2). PSM rates were 36% for group 1 and 18% for group 2, and statistically different (p=0,032). Extracapsular invasion (ECI) was significantly higher in group 1 (56,5%) than in group 2 (29,5%) (p=0,005). Multiple logistic regression analysis revealed that presence of ECI was an independent factor for PSM associated with the groups (OR: 2.512; 95% CI: 1.055-5.979). Both operation time and duration of postoperative hospitalization were significantly reduced from group 1 to group 2. A total of 11 patients (10%) had complications and one of them (0,9%) required surgical intervention. Conclusion: We can conclude that at least 50 RALP cases are needed to gain proficiency even for an experienced surgeon in laparoscopic radical prostatectomy. Our study demonstrates that surgeons experience can affect the perioperative variables but the LC does not affect PSM status in RALP.